How do swimmers pace the 400 m freestyle and what affects the pacing pattern? - Barroso, R.; Crivoi, E.; Foster, C.; Carvalho Barbosa, A. (Research in Sports Medicine, 2021)
To describe the pacing pattern of elite 400 m freestyle swimmers, understand how athletes select the first half compared to their 200-m race pace, and correlate critical speed (CS) and D` with pacing parameters. The best all-time 400 m performances were obtained, and 200 m performances were retrieved from the same competition. Twenty-four performances were selected and, when possible, 50 m-splits were obtained. CS and D` were calculated based on the 200 m and 400 m performances. Most athletes adopted a parabolic pacing pattern. Performance in the 400 m correlated with that of the 200 m (rho=0.418, p = 0.042), the % difference between 200 m performance and 200 m split correlated with CS (rho=-0.595, p = 0.002) and with D` (rho=0.808, p < 0.001). The correlation between D` and % difference between average speed and CS was nearly perfect (rho=1.000, p < 0.001). Recommendations of having the first half of the 400 m 4-5 s slower than their 200 m race do not seem to be appropriate for all swimmers and depends on physiological abilities.